Hormonal contraceptive use and depressive symptoms: systematic review and network meta-analysis of randomised trials. Issue 4 (8th June 2021) - de Wit, Anouk E.; de Vries, Ymkje Anna; de Boer, Marrit K.; Scheper, Celeste; Fokkema, Ante A.; Schoevers, Robert A.; Giltay, Erik J.
Abstract : Background: Observational studies suggest that hormonal contraceptive use may increase depressive symptoms in women, but it is unclear whether the effect is causal. Aims: To quantitatively examine the evidence from randomised clinical trials for the link between hormonal contraceptive use and depressive symptoms. Method: We performed a systematic review and network meta-analysis of randomised clinical trials comparing women randomised to any form of a hormonal contraceptive with women randomised to any other form of a (non-)hormonal contraceptive or placebo. We searched the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Web of Science, PsycINFO, EMCare and EMBASE, from inception to 1 May 2020. Certainty of the evidence was assessed with the Grading of Recommendations Assessment, Development and Evaluation approach. A random-effect Bayesian network meta-analysis was conducted, with change in depressive symptoms between baseline and three cycles as outcome. Results: This review identified 3492 records, of which 14 trials were eligible and 12 could be included in the network meta-analysis. These trials included 5833 participants (mean age per study range: 16.8–32.4 years) and compared 10 different interventions. Compared with placebo, hormonal contraceptive use did not cause worsening of depressive symptoms (standardised mean difference: median, −0.04; range, −0.17 [95% credible interval −0.46 to 0.13] to 0.13 [95% credible interval −0.28 to 0.56]). Conclusions: This study suggests that hormonal contraceptive use does not lead to an increase in depressive symptoms in adult women. Future studies should include first-time users, to confirm the results in young women.